That Religion in All Men Agree. Freemasonry in American Culture de David G. Hackett - Sánchez Solano, Esteban (Editorial de la Sede del Pacífico de la Universidad de Costa Rica, 2015)
David G. Hackett. That Religion in Which All Men Agree. Freemasonry in American Culture. Berkeley-Los Angeles-London: University of California Press, 2014. 336 pages. ISBN: 978-05-202816-7-7